The state of UK pediatric anesthesia: a survey of National Health Service activity. - Sury, M; Arumainathan, R; Belhaj, A; MacG Palmer, J; Cook, T; Pandit, J (Wiley, 2015)
This secondary analysis of the 2013 United Kingdom National Health Service (NHS) Anaesthesia Activity Survey of the Fifth National Audit Project (of the Royal College of Anaesthetists and Association of Anaesthetists of Great Britain and Ireland) shows pediatric anesthesia activity in detail. A local coordinator (LC) in every NHS hospital collected data on patients undergoing any procedure managed by an anesthetist. Questionnaires had 30 question categories. Each LC was randomized to a 2-day period. The pediatric age groups were infants, (<1 year), preschool age (1-5 year), and school age children (6-15 year). The median questionnaire return rate was 98%. The annual caseload was estimated to be 486 900 children: 36 500 infants, 184 700 preschool age, and 265 800 school age children. Almost 90% of children (1-15 year) were ASA 1 or 2 and the substantial majority underwent routine nonurgent ear nose and throat, dental, orthopaedics, or general surgery procedures; 65% were 'day cases'. One in six children were managed outside operating theater sites compared with one in 12 adults. Forty one per cent was in district general hospitals. Almost all ASA 4 and 5 children (89%) and infants (92%) were managed in specialist hospitals. 'Awake' cases and sedation accounted for only 2% of cases. There were notable differences in demography and anesthetic care compared with adults and between different age groups of children. These data enable analysis of the current state of UK pediatric anesthetic practice and highlight differences between pediatric and adult services.